Hunter syndrome follow-up after 1 year of enzyme-replacement therapy. (9th January 2013) - Puiu, Maria; Chiriţă-Emandi, Adela; Dumitriu, Simona; Arghirescu, Smaranda
Abstract : Mucopolysaccharidosis II (Hunter syndrome) is a rare x-linked disorder caused by a deficiency in the lysosomal enzyme iduronate-2-sulphatase, leading to an accumulation of the glycosaminoglycans (GAGs) dermatansulphate and heparan sulphate. The consequence of GAGs accumulation is progressive, multiorgan disease. Enzyme-replacement therapy is hypothesised to result in disease stabilisation and improved prognosis. We present a severe case of Hunter syndrome diagnosed at age 2 years and 4 months, who started enzyme-replacement therapy at the age of 3 years and 3 months. We report his evolution after 1 year of treatment. The treatment response was good and there was significant improvement in the quality of life. Owing to the rarity of Hunter syndrome, the multisystem nature and the heterogeneity of disease progression, patient care implies interdisciplinary consultations with a wide range of specialists. The best management can be provided in reference centres for metabolic diseases.